2011
DOI: 10.1590/s1808-86942011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Caudal septoplasty: efficacy of a surgical technique-preliminnary report

Abstract: Al though not being the most frequent nasal septal deviations, those of the caudal septum account for many complaints. The correction of such defects has always been the subject of much controversy, and several different operative techniques have been described. Aim:To assess the efficacy of a surgical technique for correcting caudal septal deviations. Materials and Methods:prospective study with preliminary reports of 10 patients who answered a standardized, specific questionnaire (the nasal Obstruction Sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 27 publications
0
24
0
2
Order By: Relevance
“…Also, the follow‐up period can be a shortcoming. Considering the fact that follow‐up periods were between 3 and 6 months in the previous reported studies on complications after septoplasty, the follow‐up period of the present study may be reasonable. However, a 9‐year follow‐up study has shown that both subjective and objective changes in nasal airway patency take place over time .…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Also, the follow‐up period can be a shortcoming. Considering the fact that follow‐up periods were between 3 and 6 months in the previous reported studies on complications after septoplasty, the follow‐up period of the present study may be reasonable. However, a 9‐year follow‐up study has shown that both subjective and objective changes in nasal airway patency take place over time .…”
Section: Discussionmentioning
confidence: 88%
“…As to the limitations of this study, as septoplasty does not only include the correction of caudal septum but also the correction of all deviated portions, it is difficult to insist that the result of this study is only influenced by caudal septoplasty, especially regarding nasal obstruction. Meanwhile, the change in nasal angles can be the result of caudal septoplasty because the structural problem in angle from the conventional septoplasty is minimal . Another limitation is the number of cases between the techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Severe caudal septal deviation causes stenosis of the external nasal valve and aesthetic problems [6][7][8][9][10][11][12][13][14][15][16][17][18]. In the Preoperative NOSE score and postoperative changes were shown.…”
Section: Discussionmentioning
confidence: 99%
“…Caudal septal deviation is among the causes of narrowing of the external nasal valve [6]. Even mild caudal septal deviation can cause significant obstruction [7,8]. Several techniques have been recommended for correction of caudal septal deviation due to its complexity.…”
Section: Introductionmentioning
confidence: 99%